2019
DOI: 10.1186/s12864-019-5458-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of splenocyte microRNA expression profiles of pigs during acute and chronic toxoplasmosis

Abstract: BackgroundToxoplasma gondii is an obligate intracellular parasite that infects humans and other warm-blooded animals. Previous quantitative proteomic analyses of infected host cells revealed that the expression of many host proteins is modulated by T. gondii infection. However, at present limited data are available on the differentially expressed miRNAs (DEMs) associated with the pathology and host immune responses induced by acute and chronic infection with T. gondii in pigs in vivo. In this study, high-throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 74 publications
2
34
0
Order By: Relevance
“…On the other hand, infection with the Me49 strain upregulated the expression of this miRNA. In addition, when porcine splenocytes were infected with YZ-1, miR-17 was upregulated after 25 dpi [154]. However, PAMs also presented changes in the miRNAs that regulate TNFα, indicating a predictive link between some novel miRNAs.…”
Section: Toxoplasma-host Interactionmentioning
confidence: 96%
“…On the other hand, infection with the Me49 strain upregulated the expression of this miRNA. In addition, when porcine splenocytes were infected with YZ-1, miR-17 was upregulated after 25 dpi [154]. However, PAMs also presented changes in the miRNAs that regulate TNFα, indicating a predictive link between some novel miRNAs.…”
Section: Toxoplasma-host Interactionmentioning
confidence: 96%
“…Previous studies have provided beneficial but limited insights into the porcine response to T. gondii through using methods such as high-throughput sequencing to identify the mRNA and miRNA profiles (1922), and microarrays (23). Recent research showed that T. gondii loads vary across different porcine tissues, with high parasite loads detected in the heart and lungs during acute infection, and in the heart and brain during chronic infection, regardless of the strain of the parasite (24).…”
Section: Introductionmentioning
confidence: 99%
“…Toxoplasma gondii (T. gondii), the etiological agent for toxoplasmosis, is an intracellular parasite that infects nucleated cells from all warm-blooded animals (Li et al, 2019;Hou et al, 2019). It has three infectious stages known as tachyzoite, bradyzoite, and sporozoites (within oocysts) (Dubey et al, 1998).…”
Section: Toxoplasma Gondii Infection and Host Immune Responsementioning
confidence: 99%
“…The microRNA blockade of mRNA is fundamental for protection against pathogenic virus and bacteria in plants, insects and animals (Hou et al, 2019). microRNAs interact mainly with the 3' untranslated region of their target mRNAs, controlling the translation or affecting the transcript stability favouring mRNA degradation (Hou et al, 2019). Some studies have shown that Apicomplexan parasites affect the host microRNA expression profile (Deng et al, 2004;McDonald et al, 2013;Hou et al, 2019).…”
Section: Host Micrornas During Toxoplasma Gondii Infectionmentioning
confidence: 99%